Peran Instagram dalam Pembentukan Citra Organisasi Kemahasiswaan - Friska Eldianita Nur; Zaskhya Andretta; Allisya Ridhona Aulia Djafar; Ike Junita Triwardhani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the use of Instagram as a communication tool by the DAM (Student Representative Council) of Fikom Unisba in engaging and informing students. The importance of social media platforms, particularly Instagram, for student organizations in fostering interaction and enhancing the visibility of organizational activities is emphasized. A qualitative research method was employed, utilizing interviews with key members of DAM to understand the strategies, strengths, and challenges associated with Instagram as a platform for organizational communication. The findings indicate that while Instagram effectively enhances DAM’s presence and facilitates the dissemination of important information, there is still a need for improvement in student engagement and interaction. The study concludes that Instagram plays a crucial role in strengthening the identity and credibility of student organizations, but more creative, interactive, and responsive strategies are required to boost participation and deepen student engagement. The results highlight the potential of social media in advancing organizational goals and building stronger communication channels with students. This research contributes to the field of communication studies by exploring the use of social media as a strategic tool in student organization communications.